2020
DOI: 10.1136/bmjopen-2019-030609
|View full text |Cite
|
Sign up to set email alerts
|

Rates of knee arthroplasty in patients with a history of arthroscopic chondroplasty: results from a retrospective cohort study utilising the National Hospital Episode Statistics for England

Abstract: ObjectiveThe purpose of this study was to analyse the rate of knee arthroplasty in the population of patients with a history of arthroscopic chondroplasty of the knee, in England, over 10 years, with comparison to general population data for patients without a history of chondroplasty.DesignRetrospective cohort study.SettingEnglish Hospital Episode Statistics (HES) data.Participants and interventionsPatients undergoing arthroscopic chondroplasty in England between 2007/2008 and 2016/2017 were identified. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Abram et al, in a study of almost 158,000 patients who had undergone previous chondroplasty in U.K. National Health Service (NHS) hospitals, found an increased risk of knee arthroplasty compared with that in the general British population 14 . The overall risk of knee arthroplasty within 8 years was 17.6%.…”
Section: Risk Of Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Abram et al, in a study of almost 158,000 patients who had undergone previous chondroplasty in U.K. National Health Service (NHS) hospitals, found an increased risk of knee arthroplasty compared with that in the general British population 14 . The overall risk of knee arthroplasty within 8 years was 17.6%.…”
Section: Risk Of Arthroplastymentioning
confidence: 99%
“…Long-term articular cartilage studies have shown that the rate of knee arthroplasty has ranged from 0% to 17% following regenerative cartilage surgical procedures such as microfracture, ACI, chondroplasty, or mosaicplasty [11][12][13][14] . The relative risk of knee arthroplasty in patients with a previous focal cartilage lesion versus the general population remains unknown.…”
mentioning
confidence: 99%
“…Chondroplasty as a primary procedure for focal articular cartilage defects has demonstrated inconsistent results in the literature. 9 , 18 , 19 , 20 , 21 Specifically, chondroplasty was not shown to provide symptomatic benefit as compared with observation alone in a randomized controlled trial, 19 or provide significant benefit in delaying arthroplasty. 18 However, other series have suggested that chondroplasty for articular cartilage defects less than 2 cm 2 and in the absence of concurrent meniscal pathology may be efficacious.…”
mentioning
confidence: 99%
“… 9 , 18 , 19 , 20 , 21 Specifically, chondroplasty was not shown to provide symptomatic benefit as compared with observation alone in a randomized controlled trial, 19 or provide significant benefit in delaying arthroplasty. 18 However, other series have suggested that chondroplasty for articular cartilage defects less than 2 cm 2 and in the absence of concurrent meniscal pathology may be efficacious. 9 , 21 Given the potential for meaningful clinical benefit and further informed decision-making following direct defect visualization, probing, and chondroplasty at the time of initial diagnostic arthroscopy, a single-stage definitive cartilage restoration procedure (OCA, minced cartilage allograft, etc.)…”
mentioning
confidence: 99%
“… 9 However, this technique may lead to iatrogenic damage of adjacent healthy tissue, induce localized chondrocyte death, and result in potential disease progression. 10 , 11 Furthermore, mechanical chondroplasty methods have been reported to result in poor-to-moderate clinical outcomes, with no effect on the treatment of arthrosis. 12 , 13 Instead, the instrument itself may cause a “tearing” effect on the cartilage, producing wrinkles and grooves, failing to smoothen the articular surface.…”
mentioning
confidence: 99%